Treatment of proximal fifth metatarsal fractures with an ulna hook plate. (March 2020) - Ismat, Abdullah; Rupp, Markus; Knapp, Gero; Heiss, Christian; Szalay, Gabor; Biehl, Christoph
Highlights: Hook plate treatment has demonstrated adequate and comparable results in comparison to other methods of internal fixation. Despite the small cohort size, major complications were noted in a delayed union case and a refracture case. Inpatient hospital-stay and postoperative courses were satisfactory and not prolonged. This form of fixation was not deemed to be technically difficult by the treating surgeons at our institution. The hook plate fixation method provides added benefits relating to the anatomy and fracture morphology. Abstract: Introduction: Fractures of the base of the fifth metatarsal bone present one of the commonest fractures of the metatarsal bones. Conventionally intramedullary screws and tension band wiring have been used as internal fixation methods. Lately hook plates have also served as an alternative fixation method. We hereby report on our experience with the hook plate used in treating fractures of the proximal fifth metatarsal. Methods: 21 patients treated with the hook plate for proximal fifth metatarsal fractures were assessed clinically and radiologically. Results: Average time to union in primarily treated fractures (n = 18) was 7.7 weeks (range 4.5-16 weeks). Average time to return of activities of daily living (ADLs) was 10.3 weeks (range 4.5-37 weeks). The average AOFAS midfoot score was 30.4 preoperatively and 95.2 postoperatively (p < 0.01). Conclusion: The ulna hook plate presents a suitable and adequate method of osteosynthesis used to primarily treat proximal fifth metatarsal fractures requiring surgical intervention with satisfactory post-operative outcomes.